(untitled) (Asian Business Research, 2017)
Logistics is a one of the common function that companies usually outsourced. The decision to keep this function in-house or contract with one or many third-party logistics (3PL) companies is entirely strategic and can dramatically impact any organization’s bottom line. 3PL users report an average of 44% of their total logistics expenditures are related to outsourcing. 72% of firms are increasing their use of outsourced logistics services in 2015, which is up slightly from the average reported in recent years. Most developed outsourcing logistics market belongs to the U.S. with 88%. It is followed by Asia 48%, and Europe – 46% (O’Reilly, 2010). In Italy some industries can reach the 70%, in particular food, groceries and fashion (Osservatorio Contract Logistics del Politecnico di Milano). There are many researches about logistics and large enterprises. There are less studies about Small and medium-sized enterprises (SMEs) and logistics outsourcing. SMEs play a major role in the Italian economic system. Their business activities have become an important component of the Italian economy. This paper aims to depict the adoption level of outsourcing by Italian SMEs. By direct interviews to 28 companies’ representatives we investigate which services or processes are outsourced. We investigate the reasons why companies adopt or don’t adopt the externalization. Moreover, for every company we calculate the logistics costs of simple logistics processes. In effect, we wish to compare the logistics costs communicated by the firms and the same costs calculated with ABC (Activity Based Cost) model. This research demonstrate that SMEs adopt 3PLs only for transportation. SMEs do not know all the logistics services offered by 3PLs and SMEs think the services are dedicated only to large enterprises. Finally, many companies are not able to calculate logistics costs, then they cannot compare a 3PL offer with their real costs.